Recipient Roles in Translation - Livbjerg, Inge (HERMES - Journal of Language and Communication in Business, 1999)
In spite of being taught to focus on the communicative aspect of translation, semi-professional learners have difficulty in producing translations that are truly communicative. Drawing on actual observations, this paper argues that one reason why semi-professional translators find putting themselves in the place of the addressee so difficult is that translators can be said to have as many as six recipient roles to relate to, and that they find it difficult to tell the roles apart. Below, each of the roles is described in relation to the translator, and it is suggested that confronting the students with errors seen to be rooted in a confusion of recipient roles may help them to a better understand-ing of the concept of communicative translation, and of the processes and strategies behind it. It is further suggested that the effect of acquiring such understanding depends on a combination of expectancy-, knowledge- and personality factors.